Analysis of factors affecting poverty in the special region of yogyakarta - Darsono, Susilo Nur Aji Cokro; Iriani, Latifah Dian; Putra, Dedek; Hajar, Ibnu (Indonesian Journal Publisher, 2024)
One of the provinces in Indonesia that has a fairly high poverty problem is Yogyakarta Special District Province. This is because the poverty rate of cities/districts in the Yogyakarta Special Dis-trict is higher than the provincial and national poverty rates. The study examines the influence of electricity consumption, investment, economic growth, and the District/City Minimum Wage on poverty levels in Yogyakarta Special District. The data used is panel data with cross-section data covering 5 districts/cities in Yogyakarta Province and data time series with the course of the year 2014 – 2020. The method of analysis used is a panel data regression, but the model used in this study is the Fixed Effect Model. The results show that the variables of electricity consumption and investment variables have no influence, while the economic growth variables and the minimum wage variable of the district/city have a negative and significant influence on the poverty level in the Yogyakarta Region.